Environmental administration systems approach and intervention process model - Lee, Edwin W. (Philippine Journal of Public Administration, 1982)
Environmental administration as a relatively new field of public administration still lacks a coherent body of theory, practice, and knowledge. To be responsive to the special demands and complexities of environmental programs, environmental administration needs not, only skilled administrators but managers who are able to perceive, span, and integrate all relevant factors in decision-making and program implementation. The three aspects which are deemed vital to the practice of environmental administration are: (1) conceptualization of basic concepts of the environment, changes in values, perceptions, beliefs, attitudes, and behavior; (2) coordination in all directions, vertical/horizontal, and among all levels of government, local/national; and (3) community and citizen participation in environmental and other activities. The systems approach may enable environmental administration to better deal with the intricacies involved and provide a methodology that can overcome many of its conceptual weaknesses. A proposed intervention process model, where environmental administration has an impact on the basic systems and subsystems, and on the pathways linking the systems, justifies such a positive view.